A NEW CHERRY (PRUNUS AVIUM) PEST IN TURKEY: OMALOPLIALABRATA (BURMEISTER) (COLEOPTERA: SCARABAEIDAE: SERICINI) - Ozgen, Inanc; Ahrens, Dirk (Amer Entomol Soc, 2018)
This study results from observations in cherry gardens in Elazig (Turkey: Eastern Anatolia) during 2015 and 2016. In previous studies Omaloplia labrata (Burmeister, 1855) was found feeding on leaf epidermis of leaves starting from the uppermost and youngest shoots of the growth cone, causing significant damage. This pest damages trees from the first week of June to early July, and may cause significant damage if control measures are not taken. This study is the first record of this species on cherry and harming cherry trees.
Keywords: Coleoptera; Omaloplia labrata; Prunus avium; New Pest; New Regional Record; Turkey